Application of parylene as dielectric layers in field effect transistors - Liang, Shuqin. (2011)
Single-crystal organic field-effect transistors (SC-OFETs) allow for the study of intrinsic behaviour of charges at the organic surface due to their near-perfect order and absence of grain boundaries. This project studies the use of single crystals of different organic materials for SC-OFETs with the application of parylene as the dielectric layer. Some of these materials such as TCNQ-perylene compounds have never been studied before and (perylene)2-TCNQ is a new material that has been discovered in MSE during the period of this project and is reported here for the first time. The transistor characteristics of SC-OFETs using various organic materials have been analysed and the mobility, on/off ratio and threshold voltage was reported. The highest mobility of 5.36 cm2/Vs was achieved using rubrene single crystals. Rubrene was selected for further investigations involving the parylene dielectric layer. The dependence of mobility on the thickness of the parylene dielectric was studied and it was found that in the range of approximately 0.6 – 1.3 µm the thickness did not significantly affect device performance. However, the relative consistency of device performance increased with increasing thickness. Also, the structure and surfaces of rubrene single crystals, the parylene dielectric layer and the rubrene/parylene interface were characterised. It was concluded that the choice and quality of the single crystal used and the fabrication techniques are major determinants of the performance of a SC-OFET.